The Heroine and the Meme: Participating in Feminist Discourses Online - Svenja Hohenstein (Current Objectives of Postgraduate American Studies)
This article examines the relationship between feminist participatory culture and online ativism. I argue that Internet users participate in feminist discourses online by creating memes that present popular fictional female heroes such as Katniss Everdeen (The Hunger Games“), Buffy Summers (Buffy the Vampire Slayer“), or the Disney Princess Merida (Brave“). Emphasizing specific characteristics and plot points of the respective stories, memes project, spread, and celebrate feminist ideas such as female empowerment, agency, and equality.